Foreword - Rolston, Holmes, 1932-2025, author; Springer, publisher (Colorado State University. Libraries, 2013)
The forty contributors to this anthology are wiser than Socrates. Life in an unexamined world is not worthy living either. They share their accounts, of living well in place, combining nature and culture, residing on landscapes, here termed "biocultural ethics." Ecologists bring the humanist aspects of their work to provide more compelling arguments to connect humans with nature to help solve environmental problems. There is a strong sense of "inhabiting" landscapes, not just as citizens but as residents, not just supported by ecosystem services, but of dwelling in one's country, and co-dwelling with the larger community of life, even of spiritual ties to a landscape. People and their landscape "co-constitute" each other. We get "put in our place."
Keywords: nature; culture; ecosystems; residence; landscapes; biosphere; environmental justice; environmental advocacy; climate change; religion and ecology; Earth